KNOWLEDGE OF COMMUNICATION ADAPTATION AS STABILIZATION OF PERFORMANCE ON INDUSTRIAL DISTRICT - Prayitno, Prayitno; Sutrisno, Sutrisno (UNISSULA, 2019)
Industrial districts face challenges after the advent of information technology (on line), which considersthat places are not important but for some industry players and consumers to determine. Research aims to offer practical and implementable solutions for industry players so that their performance is at a minimum before or after moving to an industrial district. Journal research methods are used in this study with journal sources originating from reputable international journals and scopus indexed. The concept of the model of knowledge of communication adaptation is our finding. The concept model is derived from the industrial district theorem and organizational knowledge typology. Knowledge of communication adaptation is a mediating alternative between government perceptions and industry players. Concept definitions are explained in this study.